Application of Income Tax on Foreign Workers in Indonesia - Aulia, Riska; Putri, Belicia Widhyana Yulia; Rasji, Rasji (CV. Rayyan Dwi Bharata, 2023)
The presence of foreign workers working in Indonesia creates rights and obligations for the foreign workers themselves. These rights and obligations are regulated by the laws and regulations in force in Indonesia, including rules relating to taxation. Foreign workers who are in Indonesia can become tax law subjects in Indonesia, so that their rights and obligations in the field of taxation apply. In order for legal regulations in the field of taxation to be implemented properly, efforts are needed to apply income tax laws to foreign workers who work in Indonesia. This paper discusses the legal basis for the imposition of income tax for foreign workers in Indonesia and the forms of accountability for violators of income tax arrangements for foreign workers in Indonesia. Based on this writing, foreign workers are a subject of income tax in Indonesia and can be subject to domestic tax or foreign tax subject. The determination is based on how long they have been in Indonesia, because they get income for what they do in Indonesia. Meanwhile, if there is an abuse related to income tax against foreign workers, in this case the tax deduction is carried out by the company where the foreign worker works, then the person who gets the sanction for the occurrence of the fraud is the party who withheld the income tax.